2020
DOI: 10.1038/s41598-020-72134-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ATP sulfurylase improves the sulfur amino acid content, enhances the accumulation of Bowman–Birk protease inhibitor and suppresses the accumulation of the β-subunit of β-conglycinin in soybean seeds

Abstract: ATP sulfurylase, an enzyme which catalyzes the conversion of sulfate to adenosine 5′-phosphosulfate (APS), plays a significant role in controlling sulfur metabolism in plants. In this study, we have expressed soybean plastid ATP sulfurylase isoform 1 in transgenic soybean without its transit peptide under the control of the 35S CaMV promoter. Subcellular fractionation and immunoblot analysis revealed that ATP sulfurylase isoform 1 was predominantly expressed in the cell cytoplasm. Compared with that of untrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Increased content of different phenylpropanoids [23] Strawberry Overexpression of a GDP-l-galactose phosphorylase (GGP) gene from Actinidia chinensis under the control of the 35S promoter A 2-fold higher content in ascorbic acid in fruits [200] Banana Expression of a Fe'i banana-derived phytoene synthase (MtPsy2a) gene under the maize polyubiquitin promoter Enhanced β-carotene content in fruit [24] Soybean Overexpression of the bacterial genes crtB (for phytoene synthase) and crtW and bkt1 (ketolase genes) under the control of seed-specific promoters Enhanced accumulation of ketocarotenoids in seeds [201] Overexpression of adenosine 5'-phosphosulfate sulfurylase 1 Higher amounts of sulfate, cysteine, and some sulfur-containing secondary metabolites in seeds [34] Overexpression of a GmDGAT2A gene driven by a seed-specific promoter of Gmole1…”
Section: Potatomentioning
confidence: 99%
See 2 more Smart Citations
“…Increased content of different phenylpropanoids [23] Strawberry Overexpression of a GDP-l-galactose phosphorylase (GGP) gene from Actinidia chinensis under the control of the 35S promoter A 2-fold higher content in ascorbic acid in fruits [200] Banana Expression of a Fe'i banana-derived phytoene synthase (MtPsy2a) gene under the maize polyubiquitin promoter Enhanced β-carotene content in fruit [24] Soybean Overexpression of the bacterial genes crtB (for phytoene synthase) and crtW and bkt1 (ketolase genes) under the control of seed-specific promoters Enhanced accumulation of ketocarotenoids in seeds [201] Overexpression of adenosine 5'-phosphosulfate sulfurylase 1 Higher amounts of sulfate, cysteine, and some sulfur-containing secondary metabolites in seeds [34] Overexpression of a GmDGAT2A gene driven by a seed-specific promoter of Gmole1…”
Section: Potatomentioning
confidence: 99%
“…or both [29], are the most common nutritional targets for biofortification strategies, though the improvement in fatty acid composition [30][31][32][33] and the increase in essential amino acids [34][35][36][37] and antioxidants [38][39][40][41] have also been recently included as aims of biofortification programs. This strategy carries multiple advantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that MGL, a putative methionine γ‐lyase, may be responsible for the accumulation of S‐methylmethionine in soybean seed (Teshima et al ., 2020). Overexpression of the cytosolic isoform of O‐acetylserine sulfhydrylase (OASS) and the plastid ATP sulfurylase isoform 1 improved the cysteine‐rich proteins and sulphur amino acid content in transgenic soybean, independently (Kim et al ., 2012b; Kim et al ., 2020). Rab5a , a small GTPase‐encoding gene, was reported to be involved in post‐Golgi trafficking of storage proteins in developing soybean cotyledons (Wei et al ., 2020b).…”
Section: Genes Responsible For Important Agronomic Traitsmentioning
confidence: 99%
“…While soybean is considered a valuable commodity of vegetable protein and oil supply for human food and animal feed, it has a limited amount of sulfur-containing amino acids such as methionine and cysteine. Therefore, several strategies, including metabolic engineering, have been undertaken to enhance the sulfur-containing amino acids in soybean seed [26,27].…”
Section: Ure 4s and Tablementioning
confidence: 99%